Relationship between prenatal mixed heavy metal/metalloid exposure and offspring cognitive and temperament development - XU Zujing; JIANG Yining; XU Jian (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To analyze the relationship between prenatal mixed heavy metal/metalloid exposure and the cognitive and temperament development of the offspring.Methods·A prospective birth cohort study was conducted in Shanghai from 2010 to 2012. Maternal venous blood samples were collected at 28‒36 weeks of gestation to measure prenatal maternal blood heavy metal/metalloid concentrations. At 24‒36 months of age, the cognitive and temperament development of the offspring were assessed by using Gesell Developmental Scale and Toddler Temperament Scale, respectively. Demographic and clinical information of mothers and children was collected via questionnaires and hospital medical records. Bayesian kernel machine regression (BKMR) models were employed to assess the effects of prenatal mixed heavy metal/metalloid exposure on toddlers' cognitive and temperament development.Results·A total of 139 mother-child pairs with complete data were included in the study. At enrollment, the mean maternal age was (29.39±3.41) years, and the mean birth weight of the infants was (3.47±0.42) kg, with 59.71% female infants. At follow-up, the average age of the toddlers was (32.91±2.69) months. Based on prior research and multivariable linear regression models, four heavy metals/metalloid—chromium (Cr), manganese (Mn), arsenic (As), and lead (Pb)—were identified as potentially associated with cognitive and temperament development in children. The median concentrations of Mn, Pb, As, and Cr in the maternal venous blood during pregnancy were 3.32, 3.60, 2.03, and 1.78 μg/dL, respectively. After adjusting for related confounders, the BKMR analyses found that when the overall concentrations of the four heavy metals/metalloid (Cr, Mn, As, and Pb) were higher than the 50th percentile, children's fine motor development quotients showed a decreasing trend as the overall concentrations of the four heavy metals/metalloid increased. Scores for adaptability, persistence, and threshold of response on the temperament scale showed a decreasing trend as well. Prenatal Mn exposure levels made the greatest contribution to the effects on children's fine motor development [PIP (posterior inclusion probability)=0.617], prenatal As exposure levels made the greatest contribution to the effects on children's persistence trait (PIP=0.656), and prenatal Cr exposure levels made the greatest contribution to the effects on children's reaction threshold trait (PIP=0.447). The contribution of all four heavy metals/metalloid to the effects on children's adaptive dimension was similar.Conclusion·Children's fine motor development and the adaptability, persistence, and threshold traits of temperament may be related to prenatal mixed exposure to heavy metals/metalloid (Mn, As, Pb, and Cr). Particular attention should be paid to the relationship between prenatal Mn exposure and children's fine motor development, and between prenatal As and Cr exposure and children's temperament development.